Adiponectin ‐11377C/G and +276G/T Polymorphisms affect Adiponectin Levels but do not Modify Responsiveness to Therapy in Resistant Hypertension. (14th January 2015) - de Faria, Ana Paula C.; Modolo, Rodrigo; Sabbatini, Andréa R.; Barbaro, Natália R.; Corrêa, Nathália B.; Brunelli, Veridiana; Tanus‐Santos, José E.; Fontana, Vanessa; Moreno, Heitor
Abstract Resistant hypertension (RHTN) is a multifactorial and polygenic disease, frequently associated with obesity. Low plasma adiponectin levels, a hormone produced by the adipose tissue, were associated with RHTN. Single nucleotide polymorphisms (SNPs) ‐11377C/G (rs266729) and +276G/T (rs1501299) in ADIPOQ (adiponectin gene) were associated with hypertension. This study evaluated the association between two SNPs (‐11377C/G and +276G/T) and adiponectin levels in RHTN. This study comprised 109 patients with RHTN genotyped for both polymorphisms. A cross‐sectional study was designed to compare features of CC homozygous versus G allele carriers for ‐11377C/G and GG homozygous versus T allele carriers for +276G/T. Office and ambulatory BP measurements were similar among genotypes subgroups in both SNPs as well as the markers of target organ damage (arterial stiffness, left ventricular mass index and microalbuminuria). Adiponectin concentrations were significantly higher in CC compared to G carrier for ‐11377C/G (CC:7.0 (4.0–10.2) versus G allele:5.5 (2.5–7.9), p = 0.04) and lower in GG compared to T carrier for +276G/T (GG:5.3 (2.3–7.7) versus T allele:7.1 (3.6–10.5), p = 0.04). Adjusting for systolic ambulatory BP, body mass index, age, gender, race and presence of type 2 diabetes, multiple linear regression analyses revealed that the minor alleles G (β‐coefficient= ‐0.14, SE=0.07, p = 0.03) and T (β‐coefficient=0.12, SE=0.06, p = 0.04) were independent predictors of adiponectin. The ‐11377C/G and +276G/T SNPs in ADIPOQ were associated with adiponectin levels in RHTN individuals.